2022
DOI: 10.21608/esugj.2022.158636.1020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effects of using biofuel blends with conventional diesel on the performance, combustion, and emission characteristics of an industrial burner

Abstract: liquid biofuels are one of the most widely utilized today, bioethanol and biodiesel are essential to the development and advancement of the industry. In this research, an experimental investigation of the effects of biofuel blends with diesel on pollutant emissions and combustion characteristics of a 350-kW industrial burner. Tested fuel blends were D100, D50B50 (50% diesel and 50% biodiesel by volume), D50B50E15 (50% diesel, 50% biodiesel, and 15% bioethanol by volume), and D50B50E25 (50% diesel, 50% biodiese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Furthermore, as the concentration of biodiesel in the mixture increases, there is a corresponding increase in the exhaust temperature. The greater oxygen content present in biodiesel can be attributable to this phenomenon when compared to standard diesel (Elkelawy et al, 2022) .…”
Section: Exhaust Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as the concentration of biodiesel in the mixture increases, there is a corresponding increase in the exhaust temperature. The greater oxygen content present in biodiesel can be attributable to this phenomenon when compared to standard diesel (Elkelawy et al, 2022) .…”
Section: Exhaust Temperaturementioning
confidence: 99%
“…Veski (2002) stated that the optimal air-to-boiler ratio must be set in order to maintain maximal boiler efficiency. Elkelawy et al (2022) found that biofuel mixtures significantly reduced emissions compared to diesel oil alone. The CO emissions decreased by 19%, 69%, and 65% for D50B50, D50B50E15, and D50B50E25 fuels, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These equipment's' accuracy may be affected by the operating conditions and operating environment as this accuracy affects the limiting errors of the measurements. So, the uncertainty of measured and calculated parameters may be estimated by the following equations 1 & 2 [68][69][70]. The precision and uncertainty analysis for different equipment's was calculated and displayed in Table 3.…”
Section: Measurements and Error Analysismentioning
confidence: 99%
“…Since fossil fuels are running out, have a lot of negative effects on the environment, and their prices are always changing, the industrial sector, which uses a lot of energy, needs fossil fuel alternatives right away. Because they come from a renewable source and are a sustainable fuel, biofuels are regarded as one of the best alternatives to conventional fuels [1,2]. In the past few years on a global scale, the Interest in the use of alternative fuels, particularly those produced from biomass residue through fermentation techniques, has increased [3,4].…”
Section: Introductionmentioning
confidence: 99%